PERSENTAGE OF INTERNAL ORGANS IN BALI PIGS FED POLLARD-CORN BASE FEED WITH ESENTIAL AMINO ACID SUPLEMENTATION - I G., Budiadnyana; Wibawa, A. A. P. P.; Sumadi, I K. (Jurnal Peternakan Tropika; Vol 8 No 2 (2020): Vol. 8 No. 2 Tahun 2020; Mei - Agustus, 2020)
This research aims to determine the effect of essential amino acid supplementation on pollard-corn base feed on internal organs weight percentages of bali boar. This research was conducted at Sindureja street, Banjar Batu Paras, Padangsambian Kaja Village, West Denpasar for 12 weeks.  The boar used are 9 bali boar with an initial average weight of 11.41 ± 0.91kg. The design was used is Completely Randomized Design (CRD) with 3 treatments and 3 replications.  The treatments were bali boar given rations yellow corn 50%, pollard 49%,  NaCl 0.5%, and mineral mixture 0.5% (P0), bali boar given rations P0 + amino acid supplementation lysine 0.75%, methionine 0.20% and tryptophan 0.07% (P1), and bali boar given rations recommendation with ME/CP ratio 2800 kcal/kg/16% (P2). The variables observed were percentage of heart weight, lung weight, liver weight, kidney weight, pancreatic weight, gastric weight, small intestine weights, and large intestine weight. The results showed that the (P1) treatments significantly (P<0.05) be able to decrease the percentage of heart weight, lung, liver, kidney, pancreatic, stomach, small intestine, and large intestine. Based on the results of this study concluded that supplementation of a essential amino acids lysine, methionine and tryptophan in corn-pollard based feeds be able to decrease the percentage of heart weight, lung, liver, kidney, pancreatic, stomach, small intestine and large intestine.   Keywords : bali boar, supplementation, amino acid, internal organ